Growth from Spores of Clostridium perfringens in the Presence of Sodium Nitrite - Labbe, Ronald G. (1970)
The method by which sodium nitrite may act to prevent germination or outgrowth, or both, of heat-injured spores in canned cured meats was investigated by using Clostridium perfringens spores. Four possible mechanisms were tested: (i) prevention of germination of the heat-injured spores, (ii) prior combination with a component in a complex medium to prevent germination of heat-injured spores, (iii) inhibition of outgrowth of heat-injured spores, and (iv) induction of germination (which would render the spore susceptible to thermal inactivation). Only the third mechanism was effective with the entire spore population when levels of sodium nitrite commercially acceptable in canned cured meats were used. Concentrations of 0.02 and 0.01% prevented outgrowth of heat-sensitive and heat-resistant spores, respectively. Nitrite-induced germination occurred with higher sodium nitrite concentrations.